Experimental Study on Application Performance of Foamed Concrete Prepared Based on a New Composite Foaming Agent. (10th February 2022) - Qiu, Youqiang; Zhang, Liujun; Chen, Yashao; Liu, Yang; Zhang, Feng
Abstract : The performance of foaming agent plays a key role in the forming quality of foamed concrete. In order to overcome the limitation of single composition of traditional foaming agent, this paper adopts the research method of multicomponent composite combined with the foaming theory and preparation technology of foaming agent, a new protein composite foaming agent was prepared using a mixture of anionic surfactant (SCA), nonionic surfactant (APG), and foam stabilizer (AR), and then, the effects of different surfactant mass ratios and foam stabilizer concentrations on the properties of composite foaming agent were studied by a series of tests. The results show that the optimal mass ratio of surfactants is mAPG : m SCA = 2 : 1, and the optimal concentration of foam stabilizer is 0.5 g/L, which verified that the self-made composite foaming agent system in this paper has the advantages of strong foaming ability, excellent foam stability, and low cost. In addition, foamed concrete was prepared on the basis of the optimized composite foaming agent system, and the influence rules of different foaming agent solution volumes, water-cement ratios, and diatomite dosages on the performance of foamed concrete were revealed through laboratory tests and SEM images. At the same time, the optimal ratio of each component required for the preparation of high-quality foamed concrete was further obtained by using the response surface analysis of compressive strength. The research results provide an important reference for the preparation of high-performance foamed concrete and corresponding foaming agent, which is beneficial for solving the disadvantages of poor foam stability in the existing foaming agents and improving the application level of foamed concrete in engineering construction.